THE POTENTIAL AND IMPLEMENTATION OF AGRICULTURAL ZAKAT IN AKEGURACI VILLAGE, CENTRAL OBA SUB-DISTRICT, THE CITY OF TIDORE ISLANDS - Nursinita Killian; Nur Azizah Rahman (IAIN Manado, 2020)
This article discusses the potential and implementation of agricultural zakat in Akeguraci village. This research aims to study the level of understanding and knowledge of the Akeguraci village farmers in the obligation of paying for zakat, especially agricultural zakat. The method used in this research is a qualitative descriptive analysis based on field research, in the form of direct observation and interviews. The result of this research indicated that the calculation and payment of the zakat of the Akeguraci village community were not following the provisions of Islamic sharia. This problem can be seen from the traditional management of zakat and the minimum level of awareness of farmers in issuing zakat so that their distribution could not be productive and on target. Public understanding reveals about zakat that must be issued is only zakat fitrah and zakat maal. While agricultural zakat has never been issued in any form. Zakat is given just as much as possible, without going through the calculation of agricultural products either by irrigation systems or purchasing water and in mobilizing workers to work to irrigate the fields